2013
DOI: 10.1007/s00038-013-0489-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health, traffic-related air pollution and noise: are associations mutually confounded? A systematic review

Abstract: ObjectivesThis review assessed the confounding effect of one traffic-related exposure (noise or air pollutants) on the association between the other exposure and cardiovascular outcomes.MethodsA systematic review was conducted with the databases Medline and Embase. The confounding effects in studies were assessed by using change in the estimate with a 10 % cutoff point. The influence on the change in the estimate of the quality of the studies, the exposure assessment methods and the correlation between road no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 51 publications
8
114
0
Order By: Relevance
“…A more recent systematic review has suggested that while there is limited evidence of confounding between noise and traffic-related air pollutants, better indicators of near-road exposures are needed. 45 If intermittent noise metrics are relevant for health impacts, their risks may be less confounded by air pollution because they are less spatially correlated with combustion-related pollutants. Our study showed a strong correlation of noise with nearby traffic density (within 100 m) which contrast to prior studies that show the larger spatial extent of combustion-related traffic pollutants, 46,47 suggesting that noise monitoring could provide opportunities to disentangle the cardiovascular risks of combustion and non-combustion traffic pollution.…”
Section: Spatial Variation In Environmental Noise and Air Pollutionmentioning
confidence: 99%
“…A more recent systematic review has suggested that while there is limited evidence of confounding between noise and traffic-related air pollutants, better indicators of near-road exposures are needed. 45 If intermittent noise metrics are relevant for health impacts, their risks may be less confounded by air pollution because they are less spatially correlated with combustion-related pollutants. Our study showed a strong correlation of noise with nearby traffic density (within 100 m) which contrast to prior studies that show the larger spatial extent of combustion-related traffic pollutants, 46,47 suggesting that noise monitoring could provide opportunities to disentangle the cardiovascular risks of combustion and non-combustion traffic pollution.…”
Section: Spatial Variation In Environmental Noise and Air Pollutionmentioning
confidence: 99%
“…This belief is derived from Islamic doctrine according which actual structure of the human is related to his/her spirit and spiritual aspect [8]. There is difference between spirit and soul based on religious resources [28].…”
Section: The Spirit Dignities In Islamic Doctrinementioning
confidence: 99%
“…We could attribute these five dignities of the spirit to the multiple degrees of the spirit including vegetal, animal, and human aspects [6]. Actually, the human has only a single spirit, and the mentioned dignities are considered in a longitudinal relation with this individual spirit which are sometimes mentioned as the "spirit forces" (Ghova-yeNafs) [8].…”
Section: The Spirit Dignities In Islamic Doctrinementioning
confidence: 99%
See 1 more Smart Citation
“…The article of Tétreault et al (2013), ''Cardiovascular health, traffic-related air pollution and noise: are associations mutually confounded? A systematic review'' has been chosen for the IJPH conference award.…”
mentioning
confidence: 99%